Nadir element katkılı seramik malzemenin Sol-jel daldırma yöntemiyle cam üzerine kaplanmasının incelenmesi - Akıncı, V. Hilmi (Fen Bilimleri Enstitüsü, 1995)
Sol-jel, tek ve çok komponentli metal alkoksit çözeltilerinin oluşturduğu jel sistemlerden cam, cam- seramik ve seramik üretimine olanak veren, son otuz yılda üzerinde yoğun çalışmalar yapılan bir yöntemi kapsamaktadır. Sol-jel'in kimyasal reaksiyonu henüz tam olarak aydınlatılmamış olmakla beraber geniş deneysel çalışmalara dayanılarak cam ve cam-seramiklerin kütle (bulk), fiber, düzcam (sheet) ve ince film şeklinde cam, metal, plastik ve oksitlenmemesi gereken seramik yüzeylere kaplanması mümkün olmuştur. Kaplamalar, kaplandıkları malzemenin optik, mekanik ve kimyasal özelliklerini önemli ölçüde modifiye ederek yeni kullanım alanları sağlarlar. Kaplama şekilleri arasında en yeni geliştirilen sınıf, 500 °C sıcaklığında elde edilen ve yapıları hakkında henüz kesin tanımlamaların verilmediği camsı filmlerdir. Camsı filmler, kimyasal bileşime ve termik işleme bağlı olarak tamamen amorf (cam) ve amorf-kristal yapı gösterebilirler. Bu çalışmada, soda-silis camının yüzeyi, sol-jel daldırma yöntemi uygulanarak, nadir element tuzu (CeCl3.7H2O) katkılı ve katkısız silisyum alkoksit çözeltilerinden 500 °C sıcaklıkta elde edilen SiO2, SiO2.CeO2 ve SiO2.2CeO2 filmleriyle kaplanmış ve başlıca çözelti bileşimi, konsantrasyonu, çekme hızı gibi deneysel parametrelere bağlı olan kaplama filmi karakteristikleri tayin edilmiştir. Kaplanan filmlerin yapısı ve yüzey mikroyapısı sırasıyla XRD ve SEM yöntemleriyle incelenmiş, geçirgenlik, absorbans, kırılma indisi gibi optik özellikleri ve kimyasal dayanıklılığı saptanmıştır. En iyi kaplama filmleri H2O/TEOS mol oranı 2.2 olan düşük viskoziteli, taze çözeltilerden 5 cm.dak"1 çekme hızıyla elde edilmiş ve çeşitli filmlerin kalınlıkları 300- 1000 nm arasında değiştiği saptanmıştır. Kaplama filmleri amorf ve amorf-kristal yapı göstermiştir. Kırılma indisi değerleri, kaplama filmlerinin renk çevirme filtreleri ve yansıtma yapmayan sistemlerde kullanılabileceği düşüncesini vermektedir.

in the present work, the preparation of SiO2/ SiO2.CeO2 and SiO2.2Ce02 films by sol-gel process was carried out and coated on -glass substrates using dip-coating technigue. Experimental parameters such as dif f erent concentration and viscosity of alkoxide solution and withdrawal speed affecting the film properties were studied. Film thickness, optical and structural characteristics, chemical and mechanical durability of coating films vere investigated. INTRODÜCTION Coating glasses, ceramics, plastics and metals with oxide films in order to gain new functions ör improve the surface characteristics of substrates have been progressed in a very productive way since the work of Dislich in 1971. Now, it is well known that, amorphous and crystalline coatings can be prepared at relatively low temperature using the metal alkoxide sol-gel process. The deposition of these glassy films greatly modifies the optical, mechanical, chemical ör electrical properties of the substrates. Coatings prepared by sol-gel dipping process (dip-coating) have s om e advantages compared to other coating technigues. it is easily applicable and amenable to coating complex shapes and also it improves chemical. durability and abrasion resistance. Besides, in the case of thin coatings, both the in-diffusion of the water reguired by hydrolysis and out-diffusion of the condensation products can be well controlled and extremely uniform, homogeneous and dense coatings can be obtained on large area surfaces. The process by which to obtain several types of coatings from metal-alkoxide solutions as well as their characterization and applications have been given in several publication [13,14,18,45,46,47]. Cerium is an important element in glass and ceramic industry and its oxide-film which is obtained with different mole ratio of cerium to other elements (mostly titanium) by sol-gel process have been studied widely though, conclusions done about the functions of cerium element in the alkoxide solutions reveal some disagreement [14]. in fact, there is very few words about SiO2-CeO2 - xii - binary system which is therefore the objective of the present work. EKPERIMENTAL 1. Apparatus ana Chemicals Shimadzu UV 160 A model of UV-Visible Spectrometer, Jeol, JSM-T330 model of Scanning Electron Microscope (SEM) and special designed dip-coating instrument, and Micro- Ostvald U-tube viscometer vere used in this research. Ali chemicals used were of reagent grade guality. 2. Methods in the sol-gel process a metal alkoxide solution is gelled through hydrolysis-polymerization reactions and converted to an oxide film by heating at relatively low temperatures. Glasses and glass-ceramics are possible to be prepared in the form of bulk, fiber sheet and coating films by sol-gel process. The sol-gel advantages are founded guite generally both on basic chemistry and practical procedure, and the combination of both turns out to be even more advantageous. The sol-gel procedure may prove to be preferred procedure for the manufacture of defined network polymers at rather low temperature [10]. in the dip-coating technigue, the substrate is dipped into the metal alkoxide solution, withdrawn vertically, evaporated at room temperature, and heated to several hundred degrees celcius. This technigue was extensively investigated by Schroeder around 1970 to provide glasses and plastics with suitable optical characteristics. The transmittance and absorbance of the coated glass slides vere determined by UV and visible spectroscopy. Composition and the micro structure of oxide films vere determined by X-Ray Diffraction And SEM methods respectively and the results vere evaluated from the XRD diagrams and SEM photographs. 3. coating Solutions Different solutions containing H20 to TEOS mole ratio of 7.4 and 2.2 vere prepared vith acid (HCl) catalyst by aging at room temperature. Each solution contained Silicon to Cerium mole ratio l to l and l to 2 respectively. Coating solutions are given in Table 1. -xiii-C\ 4. coating Procedures The glass slide after cleaned ultrasonically with alcohol is dipped into the coating solution and withdrawn vertically at three different withdrawal speed of 5 cm.min'1, 15 cm.min"1, and 23 cm.min"1. Coatings are dried in an öven at 60 °C and then sintered at 500 °C. The same procedure is repeated with 24 hours old solutions. RE8ULTS AND DISCÜSSION in order to prepare thin film in good guality, short gelation time, low viscosity, a rapid hydrolysis reaction with well aging of coating solutions are reguired. While the gelation time is short, a high water content and if an acid is catalyst, less amount of acid must be used. Therefore, many of the unknovm are in guestion f ör the study of new coating compositions. Sol-gel process itself stili carry uncertainities in chemical nature. in the present study, to use acid catalyst in coating solutions give better results than ammonium hydroxide catalyst. The use of ammonium hydroxide cause the hydrolysis reaction to proceed more rapid than condensation reaction giving stable hydrolysis species which of those give rise to inhomogenity in the resultant films. The thickness of the coating films increase with increasing withdrawal speed (Table 2) and varied exponantially with withdrawal speed. Film thickness is also increased with the increasing number of component and concentration of solution (Figüre 1,2). in some cases, film thickness of double layer coatings give lower thickness than unilayer coatings probably because of the inadeguate withdrawal speed applied för double coatings. The results of transmittance measurements show that, transmittance decreases with the increase of withdrawal speed and with cerium concentration. Yellow colour and oppalescence appear when cerium concentration increases. SiO2 coatings give higher transmittance than SiO2.CeO2 coatings. There is no distinct changes in the transmittance value of the films obtained from 24 hours old solutions. The results are shown in Table 3 and Figüre 3. The refractive index of the coating films increased with increasing withdrawal speed and thickness. X ray analysis of coating films show that a partly crystalline coating films are obtained in the case of SiO2.2CeO2 composition due to the occurrence of cerianite (CeO2). This might be originated by the contamination of sodium ion from glass substrate during thermal process, so that, sodium ions may provide the crystallization temperature för cerianite formation. -xiv- The micro structure of coating films obtained by SEM method show that, coatings prepared f rom fresh solution give thin and dense structure. Coatings obtained from old solution and solution of high cerium concentration exhibit non-homogen structure due to the products which are originated from the hydrolysis reaction and phase separation phenamenon during the thermal process. The results of chemical analysis of coating films show that, there is not distinct differences in the chemical compositions of films obtained from fresh and old coating solution. The chemical durability of coatings against acid, base, and detergent are found to be pretty good. The result of scratch test shows that, hardness of coated slides increase in öne mho degree. CONCLUSIONS The best coatings are obtained from the fresh solutions containing H20 to TEOS ratio of 2.2 with 5 cm.min"1 withdrawal speed. Film thicknesses are found to be 300 nm f ör SiO2, 350 nm f ör Si02.CeO2 and 410 nm f ör SiO2.2CeO2. The values of refractive index and transmittance of SiO2.CeO2 and SiO2.2CeO2 films in amorphous and amorphous- crystalline structures suggest that, the present coating films can be used as anti reflection layers and colour conversion filters.
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1995.
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: CAM; Glass; Coating; Ceramic coating; Sol-gel method; Glass; Coating; Ceramic coating; Sol-gel method